BOOK REVIEW: Markus Friedrich, „Die Jesuiten Aufstieg Niedergand Neubeginn“, Verlag Piper, Munchen Berlin Zurich 2016, ISBN: 9783492055390, p. 736 - OANCEA, Sever (Studia Universitatis Babeș-Bolyai Historia, 2019)
Markus Friedrich is a good knower of the Jesuit history during the Early Modern Era. Nonetheless, this book represents a huge challenge for the academia and readers, as it has a generous and informative approach, over 400 hundred years of history. The author describes the history of this order from the very beginnings, when Ignace of Loyola funded it until the election of the first Jesuit pope, Pope Francisc. The book encompasses a variety of topics and provides the reader with basic but comprehensive information on the organisation and internal order of the Societas, piety within the after Trent Era and its contribution to the Counter-Reformation, involvement in the European politics, society and culture, development and actions in the colonial world, and not at last, conversion missions, internal controversies, critics and animosities against the Jesuits, the abolishment of the order (1773) and the reorganisation after 1814. Not surprisingly, the nineteenth and twentieth century are rather presented in a resume, as the Hamburg scholar is indeed a specialist of Early Modern History. Moreover, we must take into account that the role of the Jesuits was totally different from the previous two centuries.